Plasma-Treated Water Affects Listeria monocytogenes Vitality and Biofilm Structure - Handorf, Oliver; Pauker, Viktoria Isabella; Weihe, Thomas; Schäfer, Jan; Freund, Eric; Schnabel, Uta; Bekeschus, Sander; Riedel, Katharina; Ehlbeck, Jörg (Frontiers in Microbiology, 2021)
Background: Plasma-generated compounds (PGCs) such as plasma-processed air (PPA) or plasma treated water (PTW) offer an increasingly important alternative for the control of microorganisms in hard-to-reach areas found in several industrial applications including the food industry. To this end, we studied the antimicrobial capacity of PTW on the vitality and biofilm formation of Listeria monocytogenes, a common foodborne pathogen. Results: Using a microwave plasma (MidiPLexc), 10 ml of deionized water was treated for 100 s, 300 s and 900 s (pre-treatment time), after which the bacterial biofilm was exposed to the PTW for 1 min, 3 min and 5 min (post treatment time) for each pre-treatment time, separately. Colony-forming units (CFU) were significantly reduced by 4.7 log10 ± 0.29 log10, as well as the metabolic activity decreased by 47.9 % ± 9.47 % and the cell vitality by 69.5 % ± 2.1 %, compared to the control biofilms. LIVE/DEAD staining and fluorescence microscopy showed a positive correlation between treatment and incubation times, as well as reduction in vitality. Atomic force microscopy (AFM) indicated changes in the structure quality of the bacterial biofilm. Conclusion: These results indicate a promising antimicrobial impact of plasma-treated water on Listeria monocytogenes, which may lead to more targeted applications of plasma decontamination in the food industry in the future.